Validation of conversion between mini–mental state examination and montreal cognitive assessment - Lawton, M; Kasten, M; May, M; Mollenhauer, B; Schaumburg, M; Liepelt-Scarfone, I; Maetzler, W; Vollstedt, E; Hu, M; Berg, D; Ben-Shlomo, Y (Wiley, 2016)
Introduction: Harmonizing data across cohorts is important for validating findings or combining data in meta‐analyses. We replicate and validate a previous conversion of MoCA to MMSE in PD. Methods: We used five studies with 1,161 PD individuals and 2,091 observations measured with both the MoCA and MMSE. We compared a previously published conversion table using equipercentile equating with log‐linear smoothing to our internally derived scores. Results: Both conversions found good agreement within and across the studies when comparing true and converted MMSE (mean difference: 0.05; standard deviation: 1.84; median difference: 0; interquartile range: –1 to 1, using internal conversion). Conclusions: These results show that one can get a reliable and valid conversion between two commonly used measures of cognition in PD studies. These approaches need to be applied to other scales and domains to enable large‐scale collaborative analyses across multiple PD cohorts. © 2016 International Parkinson and Movement Disorder Society